Community beliefs about tuberculosis in Ghana: Implications for the end tuberculosis global agenda - Philip Teg-Nefaah Tabong; Patricia Akweongo; Philip Baba Adongo (Cogent Medicine, 2021)
Globally, the agenda is to end tuberculosis (TB) by 2030. The emic (local) perspective about causes, signs and symptoms, and management of the disease has implications in service utilization and health-seeking. This research paper examines the local beliefs about TB and how this affects case detection and treatment. The analysis triangulates data from eight focus group discussions (N = 72), 15 in-depth interviews (IDIs) with patients with TB, and four traditional healers. TB described locally as Kɔrongkpong, kɔrongpilah (in Dagaare), and Kusibine (in Sissalla) is believed to be caused by curses, bewitchment, breaking local taboos, and a sin against the gods. The ethnosemantics depict TB as a condition of the lungs which presents with severe cough, caused by spiritual factors with fatal health outcome. In that regard, traditional medicine to exorcise the spirit is required before modern medicine can be effective. Initial symptoms such as cough and fever of TB are often self-managed and later traditional remedies sought. Furthermore, some of the signs are misconstrued for conditions such as asthma and whooping cough. The worldview of the community also dictates that these conditions have spiritual aetiologic factors and should be managed as such. This health-seeking pattern results in delays in receiving appropriate treatment. As an infectious disease, the delays in health-seeking will hinder progress towards achieving the end TB global agenda. Incorporating local beliefs into the design of interventions and social and behavioural change communication strategies can help improve case detection and treatment.